Style, Lexical Choices and Media Ideology in Selected English-Medium Newspaper Reports on Niger Delta Conflicts, 1997 – 2009 (2014)
Media reports on Niger Delta (ND) crises in Nigeria have reflected a relationship between lexico-stylistic choices and reporters‘ ideological stances. Existing studies on these reports have, however, neglected this relationship, concentrating on general stylistic, pragmatic and discourse features. These features, which are concerned more with the linguistic and contextual dimensions to the reports than the interaction between the ideology and style used by newspaper reporters, have prevented a full understanding of group-induced motivations for the crises and reports. This study, therefore, investigated the styles, contexts and strategies that manifest in selected Nigerian newspaper reports of the ND conflicts with a view to establishing the link between media ideologies and lexicostylistic choices in the reports. The study adopted Lesley Jeffries‘ critical stylistics, Teun van Dijk‘s context model, and aspects of evaluative semantics and conceptual metaphor. One hundred and fifty reports on ND conflicts were sampled: 81 from four ND-based newspapers (NDPs): The Tide, New Waves, The Pointer and Pioneer; 69 from four national newspapers (NNPs): The Punch, The Guardian, Vanguard and THISDAY between 1997 and 2009: two years before and after Obasanjo‘s 1999-2007 administration. While NDPs were selected based on their consistency in reporting on the conflicts, the NNPs were selected for their wider readership. The data were subjected to stylistic analysis. Three styles, influenced by specific ND issues and context, characterise the lexical choices in the newspaper texts – evaluative, manipulative and persuasive styles; they are achieved through four stylistic strategies: naming/describing, equating/contrasting, hypothesising, and viewing actions/events. The evaluative style is represented by emotive metaphors from three source domains – crime, hunting, and military – that name the news actors, their violent encounters, locations, and roles. The manipulative style is indexed by synonymous, hyponymous, and meronymous lexical items and intentional material actions that highlight the effect of armed struggle in the discourse. The persuasive style is realised with reiterations, lexical fields and collocations that appear as appositional and intensive relational equivalences, exploited to present the struggling situations engaged in and social labels given to the news actors. Three media ideologies are observed: propagandist, framist, and mediator ideologies. Propagandist ideology, dominated by viewing actions/events and naming/describing, is represented by reiterations and collocations used to construct the ND violence as war and threat. Framist ideology, associated with naming/describing, is enacted by reiterative and emotive labels relating to sabotaging and sanitising, which assess the news actors and their intentions in positive/negative terms. Mediator ideology, associated with hypothesising and equating/contrasting, is constructed with reiterations, lexical fields and collocations that express epistemic and boulomaic meanings, which project news actors‘ views that align with those of the news reporters‘. Thus, propagandist ideology motivates the persuasive style; framist ideology, the evaluative style, and mediator ideology, the manipulative style. The styles in newspaper reports on Niger Delta conflicts, deployed through lexical relations and stylistic strategies, are motivated by the reporters‘ ideological roles as propagandists, framists and mediators in the discourse. Therefore, there is a close interaction between lexico-stylistic choices and ideological positions in ND media reports